Pengaruh Layanan Kelompok Psikoedukasi Teknik Case Based Learning untuk Meningkatkan Individual Work Performance Student Employment - Hurina Nasibatun Sholehah; Caraka Putra Bhakti; Tri Sutanti; Arif Budi Prasetya (JURNAL BIMBINGAN DAN KONSELING AR-RAHMAN, 2026)
Individual work performance is an abstract and multidimensional construct that reflects individual behavior in the workplace that is relevant to organizational goals. This study used an experimental method with a one-group pretest-posttest design on student employment. The intervention was carried out through psychoeducation with case-based learning techniques for four sessions. The purpose of the study was to determine the effect of psychoeducational group services using case-based learning techniques to improve individual work performance. This study used a one-group pre-test post-test design. The subjects in the study were 10 student employment / student work scholarships selected using a purposive sampling technique with scale results in the low category. The research instrument was an individual work performance scale that refers to Koopmans' theory (2011). The data results were tested for validity using product moment while reliability was tested with Cronbach's alpha. The data obtained were tested using Shapiro Wilk to determine the distribution of the instrument and then retested with the non-parametric Wilcoxon signed rank test. Based on the results of the Wilcoxon test, data was obtained that there was an influence on the pretest and posttest, so it can be concluded that psychoeducational services using case-based learning techniques have an effect on increasing individual work performance of student employment. _____________________________________________________________Individual work performance merupakan konstruk abstrak dan multidimensional yang mencerminkan perilaku individu di tempat kerja yang relevan dengan tujuan organisasi. Penelitian ini menggunakan metode eksperimen dengan desain one group pretest-posttest terhadap student employment. Intervensi dilakukan melalui psikoedukasi dengan Teknik case-based learning selama empat sesi. Tujuan penelitian untuk mengetahui pengaruh layanan kelompok psikoedukasi teknik case-based learning untuk meningkatkan individual work performance. Penelitian ini menggunakan desain one-group pre-test post-test. Subjek dalam penelitian berjumlah 10 student employment / beasiswa karya mahasiswa yang dipilih menggunakan teknik purposive sampling dengan hasil skala dengan kategori rendah. Instrumen penelitian berupa skala individual work performance yang mengacu pada teori koopmans (2011). Hasil data di uji validitas dengan menggunakan product moment sedangkan reliabilitas dengan alpha cronbach. Data yang diperoleh diuji dengan menggunakan shapiro wilk untuk mengetahui distribusi instrumen dan selanjutnya diuji kembali dengan uji non parametrik wilcoxon signed rank test. Berdasarkan hasil uji wilcoxon diperoleh data bahwa terdapat pengaruh pada pretest dan posttest sehingga dapat disimpulkan bahwa layanan psikoedukasi teknik case based learning berpengaruh meningkatkan individual work performance student employment.